2015
DOI: 10.1007/s00449-015-1507-3
|View full text |Cite
|
Sign up to set email alerts
|

Continuous succinic acid production from xylose by Actinobacillus succinogenes

Abstract: ) and carbohydrate consumption rates were similar. Also, mass balance closures on xylose were up to 18.2% lower than those on glucose. A modified HPLC method revealed pyruvic acid excretion at appreciable concentrations (1.2 -) which improved the mass balance closure by up to 16.8%. Furthermore, redox balances based on the accounted xylose consumed and the excreted metabolites, indicated an overproduction of reducing power. The oxidative pentose phosphate pathway was shown to be a plausible source of the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 48 publications
2
33
2
Order By: Relevance
“…Similar to previous continuous, biofilm studies on A. succinogenes Bradfield and Nicol, 2016;Brink and Nicol, 2014;Maharaj et al, 2014), in the current study, the succinic acid yield on substrate ( Figure 2A) and the ratio of succinic acid to acetic acid (Y AASA ; Figure 2B) increased with increasing succinic acid titre (C SA ). Furthermore, the formic acid-to-acetic acid ratio (Y AAFA ) decreased with increasing C SA ( Figure 2B), indicating increased pyruvate-or formate dehydrogenase activity It has been suggested that these trends are linked to a titre-dependent shift in metabolism from a growth to a non-growth or stationary mode Brink and Nicol, 2014), with associated incomplete closures of mass and redox balances.…”
Section: Continuous Glucose and Xylose Fermentationssupporting
confidence: 89%
See 4 more Smart Citations
“…Similar to previous continuous, biofilm studies on A. succinogenes Bradfield and Nicol, 2016;Brink and Nicol, 2014;Maharaj et al, 2014), in the current study, the succinic acid yield on substrate ( Figure 2A) and the ratio of succinic acid to acetic acid (Y AASA ; Figure 2B) increased with increasing succinic acid titre (C SA ). Furthermore, the formic acid-to-acetic acid ratio (Y AAFA ) decreased with increasing C SA ( Figure 2B), indicating increased pyruvate-or formate dehydrogenase activity It has been suggested that these trends are linked to a titre-dependent shift in metabolism from a growth to a non-growth or stationary mode Brink and Nicol, 2014), with associated incomplete closures of mass and redox balances.…”
Section: Continuous Glucose and Xylose Fermentationssupporting
confidence: 89%
“…As a result, less biofilm was present in the fermenter compared to previous fermentations using a similar fermentation setup Bradfield and Nicol, 2016;Maharaj et al, 2014).…”
Section: Continuous Fermentationsmentioning
confidence: 97%
See 3 more Smart Citations